RENTABILITAS USAHA BAWANG GORENG PADA UKM LINDA DI KOTA PALU - Giovanny, Cynthia; Kalaba, Yulianti; Abubakar, Ihdiani (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
The development for Small and Medium Enterprises (SMEs) in Indonesia is quite promising. Therefore, it is essential for small and medium entrepreneurs to enhance their business vision, considering the increasingly intense global competition. This heightened competition will undoubtedly impact SMEs' performance. It is well-known that every established business shares a common goal: to maximize profits and enhance the overall value and sustainability of their business. The main objective of this study was to determine the level of business rentability achieved by SME Linda, a fried onion processing SME located in the city of Palu, based on loan capital. The selection of this location was done purposively, considering SME Linda processing fried onions that is worthy of research. The findings indicate that with an additional loan capital of IDR 100,000,000 at an interest rate of 18% per year, Linda's Fried Onion UKM achieves an average economic rentability of 37.75%. In contrast, the average return on own capital stands at 5.82%.